STATUS HUKUM IBU TIDAK MENYUSUI BAYI DAN SOLUSI PENCEGAHANNYA - Saleh, Agus Nurcholis (IAIN Batusangkar, 2018)
Much research has been done on breast milk. The results are significant. But the rate of early breastfeeding and exclusive breastfeeding is still far from expectations. Moreover, modernization and globalization have succeeded in encouraging women to work. The term, career woman. Unfortunately, the woman forgot her nature as the only supplier of ASI. Be, many babies whose rights are not fulfilled. This study relates the ASI signiﬁcance, including the legal status for women who leave ASI. This study method is literature. The author collects literature on ASI, and legal consequences for those who